An emergency-transported patient with myotonic dystrophy and syncope - Chiba, Nobutaka; Sugita, Atsunori; Watanabe, Kazuhiro; Saito, Takeshi; Mizuochi, Miki; Sakurai, Atsushi; Kinoshita, Kosaku; Mawatari, Takayuki; Nomura, Yuri; Matsuda, Keishi (KANTO Journal of Japanese Association for Acute Medicine, 2019)
A 40-year-old man was brought to the emergency department with syncope. The physical examination showed a hatchet face, bilateral eyelid ptosis, balding on the front of the head, and distal muscular weakness. In addition, there was both grip and percussion myotonia. Laboratory tests showed elevation of inflammatory markers, but creatine kinase, myoglobin, and serum electrolytes were within normal limits. Needle electromyography showed myotonic discharges and a characteristic dive bomber sound was heard. Dystrophia myotonica protein kinase (DMPK) gene analysis revealed a CTG repeat expansion of 600, confirming the diagnosis as myotonic dystrophy.　Myotonic dystrophy is a multisystem disease that can cause syncope and even sudden death. We should recognize that relatively rare diseases such as this case may be hidden in the causes of syncope.